Bimbingan Teknis Pembuatan Alat Penetas Telur Dalam Rangka Peningkatan Ketahanan Pangan Masyarakat Peternak Ayam Di Desa Lamboo Kecamatan Moramo - Budiman Sudia; Prinob Aksar; Samhuddin Samhuddin; Jaka Seru Dwi Saputra; Salimin Salimin (Vokasi Universitas Halu Oleo, 2023)
The purpose of this UHO Internal Community Partnership Service is to provide effective technical guidance on the operation of the brick making machine and transfer knowledge about the procedures for making brick making machines using a pneumatic system to the brick making community groups in Puasana Village, North Moramo District, South Konawe direct socialization and technical guidance for the operation of pneumatic molding machines. The results obtained by the group of brick-making people are an understanding of the basics of brick-making tools and the ability to operate a brick-making machine with a pneumatic system.Â